1993
DOI: 10.4278/0890-1171-7.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Community Bicycle Helmet Promotion Campaign: What Works and Why

Abstract: Future helmet campaigns should use interpersonal strategies to increase parental worry about their children being involved in a bicycle accident. Generalization of these findings is limited by the high socioeconomic status of the study participants, and by the outcome measure, which is helmet ownership, not helmet use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…DiGuiseppi, Rivara, Koepsell, and Polissar found that a community-wide campaign in Seattle, Washington, increased parental and child awareness of the need for helmets and increased helmet use (as cited in Stanken, 2000). A study in Irvine, California, also found that community-wide campaigns significantly increase helmet use (Schneider, Ituarte, & Stokols, 1993). Emergency room nurses developed a community-wide educational campaign in Florida prior to implementation of bicycle helmet legislation and found that bicycle helmet use increased, especially among 7- to 12-year-old children (Borglund, Hayes, & Eckes, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…DiGuiseppi, Rivara, Koepsell, and Polissar found that a community-wide campaign in Seattle, Washington, increased parental and child awareness of the need for helmets and increased helmet use (as cited in Stanken, 2000). A study in Irvine, California, also found that community-wide campaigns significantly increase helmet use (Schneider, Ituarte, & Stokols, 1993). Emergency room nurses developed a community-wide educational campaign in Florida prior to implementation of bicycle helmet legislation and found that bicycle helmet use increased, especially among 7- to 12-year-old children (Borglund, Hayes, & Eckes, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…School nurses can include families, community members, and community resources in educational interventions. For example, it is noted that parents who are knowledgeable about injury and accident statistics associated with bicycle riding are more inclined to encourage helmet use in their children (Schneider et al, 1993). Therefore, teaching strategies should include sharing information with parents.…”
Section: Implications For School Nursing Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Such advice has been shown to increase the likelihood of bicycle helmet ownership for children. 9 Responsibility for strengthening individual knowledge and skills need not be limited to physicians and human service professionals. Bicycle sales people can demonstrate how to properly fit a helmet for optimum safety.…”
Section: (1) Strengthening Individual Knowledge and Skillsmentioning
confidence: 99%
“…Bicycle related injuries are a major cause of death and disability in children under 18 years of age. In the US, traffic related bicycle mishaps accounted for approximately 580 000 emergency department visits, 23 000 hospital admissions, and over 800 deaths every year between 1987 and 1991.'…”
mentioning
confidence: 99%